Influence of organization ethos on research competence of teachers in higher education institutions - Srivastava, Kiran; Prakasha, G. S. (International Journal of Evaluation and Research in Education (IJERE), 2024)
The standards of research depend on the maintenance and coordination of research activities that are conducted by the teachers in higher education institutions. The flexibility in ordinances and statutes empowers the higher education institutions to frame the guidelines that empower the research competence of the teachers. This descriptive research has collected the data from 451 regular teachers of higher education institutions from different areas of discipline for the research. The results of the study show that there is a significant difference in measures of the perceptions of the teachers towards the relationship between organization ethos and research competence in higher education institutions. The study indicates the practical and academic importance for teachers to enhance research performance of higher education institutions.